Pengaruh Kompetensi Kerja, Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan PT Nasatech Sukses Abadi - Angles William; Purnama Yanti Purba; Vina Prenita; Melinawaty Lumban Tobing (COSTING : Journal of Economic, Business and Accounting, 2020)
Employees have a big role in fulfilling fluency in the field of organization. Organizations need human resources to develop their businesses. This study aims to examine and analyze the effect of competence, work discipline, and job satisfaction on employee performance at PT Nasatech Sukses Abadi Medan. The phenomenon of performance instability that can be seen from the achievement of the company's targets caused by lack of competence and employee work discipline and a decrease in employee job satisfaction is the background of this study. The research method used is a quantitative approach, the type of research is quantitative descriptive, and the nature of this study is descriptive explanatory. The data analysis method is multiple linear regression analysis. The sampling technique uses the saturation sampling method. The study sample was 83 employees. The results of this study prove the existence of a significant and positive influence on competence, work discipline, and job satisfaction have a positive and significant effect on employee performance at PT Nasatech Sukses Abadi Medan. Keywords: Competence, Work Discipline, Job Satisfaction, Employee Performance